FATORES A SEREM CONSIDERADOS PARA O LANÇAMENTO DE NOVA MARCA DE CAFÉ ORGÂNICO - Lopes, Dayanny Carvalho (2011)
The demand for organic products increases worldwide and creates market opportunities in various regions of the world, especially for small and medium producers, including communities of family farmers and various other components of the production chain, which may help the development of rural areas close to large urban centers and export corridors. It is observed that consumers are more concerned with issues related to health and environment, and in this regard the market lacks sustainable products. In face of the consumers concern about welfare, Coopfam will launch onto the market a new sustainable product: DaTerra organic coffee. A research was then carried out in the supermarkets of Machado and Poço Fundo, MG, by means of a questionnaire, to verify the factors to be considered for launching a new product, as is the main purpose of this study: to launch a new brand of coffee. The results showed that institutional clarification campaigns should be formulated, due to the lack of information of consumers with regard to organic coffee, and strategies for launching this product will aim at consumers who are unaware of organic products.